Consumers’ Evaluation of Animal Welfare Labels on Poultry Products - Rexanna Powers; Nan Li; Courtney Gibson; Erica Irlbeck (Journal of Applied Communications, 2020)
As the public has expressed increasing concerns regarding the humane raising and handling of farm animals, the U.S. Department of Agriculture and industry organizations have developed a series of standards enforcing animal welfare in the poultry industry. Labels and value-added claims were created and defined to differentiate products and to inform consumers’ purchasing decisions. This study identified five labels related to animal welfare that are frequently found on food packages in the U.S. grocery stores, including both the mandatory labels and third-party, voluntary labels. Using a controlled online experiment (N=249), we examined the labels’ effects on consumers’ perception of humane treatment and purchasing tendencies toward egg products. Results showed that while most consumers lack knowledge regarding the labels’ meaning and certification standards, they rely on the labels with simplistic terms (e.g., "certified humane," "cage free") as heuristic cues to judge the ethical treatment of hens on the farm. However, the selected labels did not lead consumers to pay a higher premium for the labeled products. We discussed the implications for regulators, food marketers, and agricultural communicators.
Keywords: animal welfare; humane treatment; food labeling; poultry industry; food marketing